Partisipasi Politik Masyarakat Desa Rias pada Pemilu 2019 - Khairul Amin; Siti Ikramatoun; Halik (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2021)
This article aims to describe the political participation of the Rias Village community in the 2019 election and the conditions that affect this political participation. This article uses a descriptive approach with a qualitative method. The data in this article are the results of interviews and relevant literature studies. This study found that Rias Village's voter turnout is higher than the average voter turnout at the sub-district, district, provincial and national levels. That participation correlated positively with political participation in the sub-district level to the national level. The conditions that affect the participation of the Rias Village community in the 2019 elections are the political dynamics of the presidential election, legislative candidates from within Rias Village, experience, and community political knowledge. This finding confirms that political participation is related to other socio-political contests that develop in society.